Prevalence of dental anomalies in deciduous dentition and its association with succedaneous dentition: A cross-sectional study of 4180 South Indian children - G Shilpa; Niraj Gokhale; Sreekanth Kumar Mallineni; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2017)
Objective: The objective of this study was to estimate the prevalence of dental anomalies in primary dentition of Indian population. Materials and Methods: This cross-sectional study was conducted on 4180 children in the age of 2-6 years. Anomalies were classified based on Kreiborg criteria. The term "double tooth" was used to avoid misinterpretation between gemination. and fusion. Patients having radiographs were also examined for associated dental anomalies in permanent dentition. The occurrence and gender prevalence were evaluated using descriptive statistics. Results: About 95. (2.27%) children exhibited at least one dental anomaly. Thirty.seven children showed 51 missing teeth. (0.88%), mostly in lower right incisors with a statistically significant difference between arches. (P = 0.0056) Nine children. (0.21%) had supernumerary teeth commonly in the right maxilla. Two cases of oligodontia. (0.04%) and talon cusps. (0.04%) and one case of triple tooth. (0.02%) were observed. Forty children. (0.95%) had 43 double teeth mostly in the right mandible with a statistically significant difference between the arches. (P = 0.0105). No significant difference was observed based on gender and arch, but they were statistically significant between the right and left sides. (P = 0.018). Among the children with radiographs available, 45% showed anomalies in the succedaneous dentition. Conclusions: The prevalence rates of children with double tooth, hypodontia, and hyperdontia in our study are 0.95%, 0.88%, and 0.21%, respectively. The overall prevalence rate of anomalies among boys was higher than girls.